1987
DOI: 10.1002/eji.1830170208
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation by anti‐idiotypic antibody: mechanism of interaction with antigen‐reactive T cells

Abstract: It has been shown that the activation of T cells by an anti-idiotypic antibody (anti-Id) TB71 containing an internal image of the corresponding mycobacterial antigen (38 kDa) was achieved by the interaction of anti-Id TB71 with the T cell receptor complex (CD3/Ti). The accessory cell requirement in this response could not be replaced by anti-Id TB71 coupled to Sepharose beads and was not inhibited by Fc receptor blockade. When taken together with the finding that anti-Id TB71-induced proliferation of a T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The in vitro proliferation that is observed using monovalent Fab fragments or isolated H chains rules out the possibility that our anti-Id is causing proliferation of these primed cells by crosslinking receptors on the T cells, as has been described with the anti-CD3 antibody (19). This is consistent with other reports of anti-Id activating antigenprimed T cells (17,18). Kees et al (17) have shown that a rabbit anti-Id that mimics a 38-kD protein purified from Mycobacterium tuberculosis could stimulate human PBL obtained from either M. tuberculosis patients or BCG-vaccinated individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The in vitro proliferation that is observed using monovalent Fab fragments or isolated H chains rules out the possibility that our anti-Id is causing proliferation of these primed cells by crosslinking receptors on the T cells, as has been described with the anti-CD3 antibody (19). This is consistent with other reports of anti-Id activating antigenprimed T cells (17,18). Kees et al (17) have shown that a rabbit anti-Id that mimics a 38-kD protein purified from Mycobacterium tuberculosis could stimulate human PBL obtained from either M. tuberculosis patients or BCG-vaccinated individuals.…”
Section: Discussionsupporting
confidence: 91%
“…The synthetic peptide S(139-147), which represents a partial a determinant epitope, could also stimulate anti-Id-primed T cells in vitro, further demonstrating the fidelity with which our anti-Id mimics the a determinant. It has been shown by others that anti-Id antibodies can influence specific T cell reactivity (15)(16)(17)(18). Thus, in the reovirus system, Sharpe et al (16) have demonstrated that an internal image anti-Id that was raised against an antireovirus type 3 mAb could trigger T cell immunity (delayed type hypersensitivity and CTL responses) to reovirus type 3 in naive mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that anti-idiotypic antibodies are taken up by dendritic cells in the skin, and presented to the immune system in association with class I and II major histocompatibility complex (MHC) glycoproteins, and costimulatory molecules 15. Cytotoxic and helper T cell responses capable of targeting the TAA that 105AD7 mimics may thus be elicited.…”
Section: Discussionmentioning
confidence: 99%
“…A special case of cross-reactivity is the induction of epitope-specific immune responses by anti-idiotype (Id) antibodies, acting as the epitope’s “internal image.” This was demonstrated for both mouse and human CD4 T-cell responses, using rabbit anti-Ids raised against PstS1-specific mouse mAbs (59, 60). However, the corresponding structural determinants remained undefined and the approach has been overtaken by the more exact recombinant DNA and synthetic peptide technologies.…”
Section: Cross-reactivity Of Mycobacterial Epitopesmentioning
confidence: 93%